Designing Democratic Institutions : Nomos XLII. - Shapiro, Ian (NOMOS Series., 2000)
As the principles and practices of democracy continue to spread ever more widely, it is hard to imagine a corner of the globe into which they will not eventually penetrate. But the euphoria of democratic revolutions is typically short-lived, and usually followed by disgruntlement and even cynicism about the actual operation of democratic institutions. It is widely accepted that democracy is a good thing. However democrats have much work to do in improving the performance of democratic institutions. The essays in this volume focus on this difficult and vital challenge: how can we improve the de.